Effects of the synbiotic composed of mangiferin and Lactobacillus reuteri 1–12 on type 2 diabetes mellitus rats - Meng, Fanying; Zhang, Fan; Meng, Meng; Chen, Qiuding; Yang, Yaqin; Wang, Wenbo; Xie, Haina; Li, Xue; Gu, Wen; Yu, Jie (Frontiers in Microbiology, 2023)
Many synbiotics are effective for the prevention and treatment of type 2 diabetes mellitus (T2DM). In the treatment of T2DM, synbiotics often regulate the composition of intestinal flora, which autoinducer-2 (AI-2) may play an important role. Whether the changes of intestinal flora are related to AI-2 during synbiotics treatment of T2DM is a topic worth studying. We elucidated the effects of synbiotic composed of mangiferin and Lactobacillus reuteri 1–12 (SML) on T2DM rats. Male Spraque-Dawley rats were injected intraperitoneally with streptozotocin (STZ) and randomly grouped. After that, biochemical parameters, intestinal flora, fecal AI-2, and intestinal colonization of L. reuteri were detected. The results showed that SML had a hypoglycemic effect and mitigated the organ lesions of the liver and pancreas. Also, SML regulated biochemical parameters such as short chain fatty acids (SCFAs), lipopolysaccharides (LPS), intercellular cell adhesion molecule-1 (ICAM-1), and tumor necrosis factor-α (TNF-α). On the other hand, the proportion of probiotics, such as Lactobacillus acidophilus, L. reuteri, Bifidobacterium pseudolongum, Lactobacillus murinus, and Lactobacillus johnsonii, were elevated by the treatment of SML. In addition, SML promoted the colonization and proliferation of L. reuteri in the gut. Another thing to consider was that AI-2 was positively correlated with the total number of OTUs sequences and SML boosted AI-2 in the gut. Taken together, these results supported that SML may modulate intestinal flora through AI-2 to treat T2DM. This study provided a novel alternative strategy for the treatment of T2DM in future.